Sell the oil deposits!: A financial proposal to keep the oil underground in the Yasuni National Park, Ecuador - Santiago Bucaram; Mario Andrés Fernandez; Diego Grijalva (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The Yasuni National Park is a protected area located in the Amazon region of Ecuador and is recognized as one of the most biodiverse regions in the world. In recent years the park has received much attention due to the media exposure of the Yasuni-ITT Initiative. This Initiative proposed a moratorium on oil activities in the Ishpingo-Timbococha-Tiputini (ITT) blocks within the Yasuni National Park, in exchange for US3.6 billion in compensation over ten years, to be paid by the international community. In this paper we first conduct a feasibility analysis of the ITT Initiative and show that it was severely flawed from its inception. Second, we develop a financial approach for a 'New ITT Initiative'. We propose the sale or leasing of the rights of extraction of the oil deposits in the Park as a feasible strategy to keep the oil underground and consequently to protect the Yasuni National Park's ecosystem services. Our proposal is much more simplified and transparent than the original ITT Initiative and could be easily implemented through existing financial mechanisms.
Keywords: Q35; Q51; Q56; Q57; 330; additionality; uncertainty; permanence; leakage; discount; Monte Carlo